Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia - Herrera-Flórez, Andrés Fabián (Zootaxa, 2018)
Three new species of Grotea Cresson 1864 from Colombia are described: Grotea llanera, G. santandereana and G. cundinamarquesa. An identification key to Colombian species of this genus is given.